Varying behavioral differences and correlates of HPV infection among young adolescents in Benue state, Nigeria - Evelyn Erdoo Orya; Kayode Khalid Bello; Sidney Sampson; Esther Awazzi Envuladu; Hilary I. Okagbue (BMC, 2024)
Abstract Background Human Papillomavirus (HPV) infection is a significant public health concern globally, especially in low- and middle-income countries. In Africa, including Nigeria, HPV prevalence is high, contributing to a substantial burden of cervical cancer. Despite challenges, massive HPV vaccination campaigns in Africa show promise for preventing cervical cancer cases. In Benue State, Nigeria, limited research exists on several aspects of HPV knowledge and attitudes towards HPV among secondary school students. This study aims to bridge this gap by assessing HPV knowledge, prevention practices, willingness to uptake HPV vaccination, and associated attitudes and behaviors among secondary school students in the state. Methods The cross-sectional study was conducted among adolescents aged 10-19 years in six secondary schools in three local government areas (LGAs) in Benue State, Nigeria. Two-stage sampling was used to select the LGAs and schools, with a final sample size of 591 students. The selected schools represent both junior and senior secondary school levels and span across the three senatorial districts of the state. Data were collected using a self-administered questionnaire covering sociodemographic characteristics, HPV knowledge, prevention practices, and willingness for HPV vaccination. Statistical analyses included univariate analyses and tests of association, with significance set at p < 0.05 or 0.001 depending on the level of the stringency of the evidence required. Data were analyzed using SPSS version 25. Results Only 35.4% of the participants were males, and 86.8% were between the ages of 10 and 16. Only 24.7% acknowledged that HPV can be transmitted during sexual intercourse, and 36.2% recognized that HPV can be transmitted via skin-to-skin contact. 48.1% noted that HPV can cause cervical cancer. Half (50.9%) acknowledged that early sexual debut increases the risk of acquiring HPV, while only 28.1% recognized vaccination as a preventive strategy against HPV infection. Only 35% correctly stated the best time for the HPV vaccine. In assessing the practice of HPV prevention, 14.9% are in a sexual relationship and 10.3% admitted to not using condoms during sexual intercourse. Also, 11.8% have had STIs, and 27.2% have previously undergone HIV screening. Various bivariate analyses showed some varying behavioral differences and correlates of HPV infection among young adolescents in Benue State, Nigeria. Conclusions This study provides valuable insights into HPV knowledge, prevention practices, and willingness to uptake HPV vaccination among secondary school students in Benue State, Nigeria. The significance of the differences and correlates was discussed using themes. The research has unpacked complex relationships that could have public health implications for researchers and policymakers. Moreover, ten actionable policy recommendations were prescribed. Several interventions and areas for further study were proposed.